2017
DOI: 10.1007/s00192-017-3511-4
|View full text |Cite
|
Sign up to set email alerts
|

Uterus-sparing vaginolaparoscopic sacrocolpopexy for apical pelvic organ prolapse

Abstract: By eliminating all forms of intraperitoneal suturing, performing a posterior colpotomy, and the advent of tackers without evidence of sacral ostitis, VLS seems to be a simple, feasible, effective, and fast approach for treating POP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In the one study, which reported scores for the ICIQ-VS pain domain, women in the sample had a younger mean age 19 (38 years) compared to women in the other studies reporting on pain whose mean ages were all in the fifties and sixties. 29 , 31 , 32 , 35 This study reported a high level of pain with POP; however, the study sample of 15 women was very small.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…In the one study, which reported scores for the ICIQ-VS pain domain, women in the sample had a younger mean age 19 (38 years) compared to women in the other studies reporting on pain whose mean ages were all in the fifties and sixties. 29 , 31 , 32 , 35 This study reported a high level of pain with POP; however, the study sample of 15 women was very small.…”
Section: Resultsmentioning
confidence: 79%
“…The POP-Q stage was reported in three ways: as a grouping of 2 or more stages (i.e. women with POP stage 2–4), 27 , 30 , 31 , 34 , 37 , 38 separately reporting POP-Q stage for each compartment for each participant 23 or separately reporting the dominant compartment POP-Q stage. 22 , 24 26 , 28 , 29 , 32 , 33 , 35 , 36 , 39 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations